Decreased scene-selective activity within the posterior intraparietal cortex in amblyopic adults - Malladi, Sarala N.; Skerswetat, Jan; Schmidt, Marianna E.; Tootell, Roger B. H.; Gaier, Eric D.; Bex, Peter J.; Hunter, David G.; Nasr, Shahin (Frontiers in Neuroscience, 2025)
IntroductionAmblyopia is a developmental disorder associated with reduced performance in visually guided tasks, including binocular navigation within natural environments. To help understand the underlying neurological disorder, we used fMRI to test the impact of amblyopia on the functional organization of scene-selective cortical areas, including the posterior intraparietal gyrus scene-selective (PIGS) area, a recently discovered region that responds selectively to ego-motion within naturalistic environments.MethodsNineteen amblyopic adults (10 females) and thirty age-matched controls (15 females) participated in this study. Amblyopic participants spanned a wide range of amblyopia severity, based on their interocular visual acuity difference and stereoacuity. The visual function questionnaire (VFQ-39) was used to assess the participants’ perception of their visual capabilities.ResultsCompared to controls, we found weaker scene-selective activity within the PIGS area in amblyopic individuals. By contrast, the level of scene-selective activity across the occipital place area (OPA), parahippocampal place area (PPA), and retrosplenial cortex (RSC) remained comparable between amblyopic and control participants. The participants’ scores on “general vision” (VFQ-39 subscale) correlated with the level of scene-selective activity in PIGS.DiscussionThese results provide novel and direct evidence for the impact of amblyopia on scene processing within the human brain, thus enabling future studies to potentially link these changes across the spectrum of documented disabilities in amblyopia.